Multimoda Analysis, Information Technology, Communication and Order Consolidation on Logistics Cost Efficiency - Tohir, Muhammad; Primadi, Andri; Allsya, Christina (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The Influence of Multimodal Transport, Information and Communication Technology, and Order Consolidation on Logistics Cost Efficiency is a scientific literature review article within the field of logistics. The aim of this article is to build hypotheses regarding the influence of independent variables on the dependent variable, which will be used in future research. The research objects include online media libraries such as Google Scholar, Semantic Scholar, Elsevier, Zotero, and other online journal platforms. The analysis uses a qualitative descriptive approach. The results of this article are: 1) Multimodal transport influences logistics cost efficiency; 2) Information and communication technology influences logistics cost efficiency; and 3) Order consolidation influences logistics cost efficiency.